AN ANALYSIS OF A TEACHER'S QUESTIONS IN EFL CLASSROOM: A Qualitative Case Study of English Teacher in Public Junior High School in Bandung - Jannah, Eka Raudhatul (2013)
A qualitative research design was employed in this study. The data were obtained from classroom observation for five learning sessions and one interview session. The data collected from classroom observation were transcribed and then analyzed by using the Taxonomy theory of Bloom (1956) in dividing several cognitive domains to construct the purposes of the teacher's questions asked in classroom activities. Meanwhile, the students' responses to teacher's questioning behavior were analyzed based on Suherdi framework (2007). The findings of this study shown that only four of all cognitive domains of Bloom's questions taxonomy were asked by the teacher especially in three lower cognitive domains such as knowledge, comprehension and application or those are in display questions and one of the three higher cognitive domains such as analysis or those are in referential question. Moreover, the study revealed that those questions or cognitive domains will not make students produce longer responses unless the teacher is able to encourage the students to elaborate further rather that only accepting responses brief or less complex responses. On the other hand, to facilitate the second language development of students and bring about more conversational forms of whole class teaching, the students should be asked to expand their critical thinking and opinions as the responses to the moves among teacher and students. Finally, it is recommended that a study be conducted in broader scope of criticizing the teacher's questions and delivering strategies. In addition, the implication of this study is that teacher should be given a training program to develop teachers' questioning techniques so that more complex selection of questions will appear. Keywords: Teacher's Questioning Behavior, Students' Responses, Junior High School Desain penelitian kualitatif diterapkan pada penelitian ini. Data dikumpulkan dari observasi kelas sebanyak lima sesi pembelajaran serta satu sesi wawancara. Data yang dikumpulkan dari observasi kelas telah ditulis dan kemudian dianalisis dengan menggunakan Teori Taxonomy Bloom (1956) dalam membaginya ke dalam beberapa ranah kognitif untuk mengetahui tujuan dari pertanyaan-pertanyaan guru yang ditanyakan pada aktifitas-aktifitas kelas. Sementara, respon-respon siswa terhadap pertanyaan-pertanyaan guru akan dianalisis berdasarkan teori Suherdi (2007). Hasil dari penelitian ini menunjukkan bahwa hanya empat dari keseluruhan ranah kognitif dari taksonomi pertanyaan Bloom telah ditanyakan oleh guru terutama pada tiga ranah kognitif yang terendah seperti knowledge, comprehension dan application atau display questions dan satu dari tiga ranah kognitif lebih tinggi seperti analysis atau referential questions. Selain itu, penelitian juga mengungkapkan bahwa keseluruhan pertanyaan atau ranah kognitif tersebut tidak akan membuat para siswa menghasilkan respon-respon lebih panjang kecuali kalau guru mampu untuk mendorong para siswanya untuk lebih menjelaskan daripada hanya menerima respon tersebut dengan singkat atau respon yang kurang kompleks. Di samping itu, untuk memfasilitasi pengembangan bahasa kedua bagi para siswa dan membuat atmosfir kelas yang lebih bersifat percakapan, para siswa harus ditanya untuk mengembangkan pemikiran kritis dan pendapatnya sebagai respon dari percakapan yang dilakukan antara guru dan siswa. Kesimpulannya, direkomendasikan untuk penelitian yang dilakukan pada ruang lingkup yang lebih luas dalam mengritisi pertanyaan-pertanyaan guru serta strategi penyampaiannya. Dan juga, implikasi penelitian ini adalah guru harus diberikan sebuah program pelatihan untuk mengembangkan teknik bertanya guru sehingga pemilihan pertanyaan yang kompleks akan muncul. Kata kunci: Perilaku Bertanya Guru, Respon Siswa, Sekolah Menengah Pertama